Hawaiian Surfing Traditions from the Past - Clark, John R. K. (University of Hawaii Press, 2011)
Hawaiian Surfing is a history of the traditional sport narrated primarily by native Hawaiians who wrote for the Hawaiian-language newspapers of the 1800s. An introductory section covers traditional surfing, including descriptions of the six Hawaiian surf-riding sports (surfing, bodysurfing, canoe surfing, body boarding, skimming, and river surfing). This is followed by an exhaustive Hawaiian-English dictionary of surfing terms and references from Hawaiian-language publications and a special section of Waikiki place names related to traditional surfing. The information in each of these sections is supported by passages in Hawaiian, followed by English translations. The work concludes with a glossary of English-Hawaiian surfing terms and an index of proper names, place names, and surf spots